The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00359-019-01347-z
|View full text |Cite
|
Sign up to set email alerts
|

A matter of taste: the adverse effect of pollen compounds on the pre-ingestive gustatory experience of sugar solutions for honeybees

Abstract: In addition to sugars, nectar contains multiple nutrient compounds in varying concentrations, yet little is known of their effect on the reward properties of nectar and the resulting implications for insect behaviour. We examined the pre-ingestive responses of honeybees to sucrose solutions containing a mix of pollen compounds, the amino acids proline or phenylalanine, or known distasteful substances, quinine and salt. We predicted that in taste and learning assays, bees would respond positively to the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Given that it is an essential nutritional component for insects (House, 1965), its potential recognition by bees as a palatable substance would be expected. In line with this, previous studies have shown that the presence of other amino acids offered during or before training affects honeybee learning performance (Kim and Smith, 2000;Simcock et al, 2014;Nicholls et al, 2019). In addition, another study has shown that bees can identify umami taste, and has characterized a chemosensory taste receptor that responds to L-amino acids (AmGr10), among which is L-arginine (Lim et al, 2019).…”
Section: Effects Of Single Compounds On Learningmentioning
confidence: 65%
“…Given that it is an essential nutritional component for insects (House, 1965), its potential recognition by bees as a palatable substance would be expected. In line with this, previous studies have shown that the presence of other amino acids offered during or before training affects honeybee learning performance (Kim and Smith, 2000;Simcock et al, 2014;Nicholls et al, 2019). In addition, another study has shown that bees can identify umami taste, and has characterized a chemosensory taste receptor that responds to L-amino acids (AmGr10), among which is L-arginine (Lim et al, 2019).…”
Section: Effects Of Single Compounds On Learningmentioning
confidence: 65%
“…We used adult worker bees sourced from 3 commercial B. impatiens colonies (BioBest LTD, Leamington, Ontario, Canada) and 6 treatment combinations: sterilization treatment (GI, EO, or no treatment) crossed by pollen type (wildflower pollen mix or monofloral sunflower pollen) with 10 bees/colony/treatment combination (10/colony × 3 colonies × 6 treatment combinations = 180 bees total). Differences in the nutritive quality, secondary metabolite content, and freshness of stored pollen can influence palatability and preferences by bees (Vaudo et al 2016a, Carroll et al 2017, Nicholls and de Ibarra 2017, Nicholls et al 2019). We thus included both the wildflower pollen mixture and monofloral sunflower pollen to assess whether pollen sterilization treatment differentially affected palatability of 2 distinct pollen diets.…”
Section: Effect Of Sterilization On Pollen Quality and Palatability: ...mentioning
confidence: 99%
“…2006; Nicholls et al . 2019) and tarsi as well as proboscis of Eristalis hoverflies (Wacht et al . 1996, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Bees can also perceive tactile stimuli via their antennae (Gack 1981). Proline is a common amino acid present in pollenkitt (Linskens & Schrauwen 1969;Mattioli et al 2018) and thus a potential candidate for a universal chemical pollen cue that can be perceived with the antennae of bumblebees (Ruedenauer et al 2019), honeybees (Carter et al 2006;Nicholls et al 2019) and tarsi as well as proboscis of Eristalis hoverflies (Wacht et al 1996(Wacht et al , 2000. However, proline has never been found in pollen-mimicking structures (Biancucci et al 2015), reinforcing that the visual cue is predominant in the PASAM system as compared to any other chemical cue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation